Pengaruh Komposisi Nutrisi Dan Harga Makanan Sehat Terhadap Keputusan Pembelian Produk Nugget Pada Gen Z Program Studi S1 Manajemen Fakultas Ekonomi Dan Bisnis Universitas Dharma Andalas - Nisya Cesaryani Rahmasari; Mohammad Abdilla; Yenni Del Rosa; Nofri Yendra; Idwar Idwar (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2026)
The purpose of the study was to determine the effect of perceived ease of use, perceived usefulness, attitude toward using and actual usage on the consumptive eating patterns of Gen Z of Dharma Andalas University partially and simultaneously. Primary data sources from field research and secondary data from library research. The type of research is associative with a quantitative approach. The research population was 90 people, the number of research samples was 90 people determined by total sampling. Data collection methods used questionnaires, interviews and observations. Before the data was processed, it met all instrument tests and classical assumption tests for the research variables perceived ease of use (X1), perceived usefulness (X2), attitude toward using (X3), actual usage (X4) and consumptive eating patterns (Y). The results of multiple linear regression obtained Y = 0.096 + 0.446 X1 + 0.302X2 + 0.279X3 + 0.251X4 + e. The results of partial and simultaneous hypothesis testing at a significance level of 5% show that perceived ease of use, perceived usefulness, attitude toward using and actual usage have a significant positive effect on the consumptive eating patterns of Gen Z at Dharma Andalas University. Abstrak Tujuan penelitian mengetahui pengaruh komposisi nutrisi dan harga makanan sehat terhadap keputusan pembelian produk nugget pada gen Z di Fakultas Ekonomi dan Bisnis Universitas Dharma Andalas secara parsial dan simultan. Sumber data primer dari field research dan data sekunder dari library research. Jenis penelitian bersifat asosiatif dengan pendekatan kuantitatif. Populasi penelitian 90 orang, jumlah sampel penelitian 90 orang ditentukan secara total sampling. Metode pengumpulan data menggunakan angket, wawancara dan observasi. Sebelum data diolah memenuhi semua uji instrumen dan uji asumsi klasik untuk variabel penelitian komposisi nutrisi (X1), harga makanan sehat X2) dan keputusan pembelian produk nugget (Y). Hasil regresi linier berganda didapat Y = 2.590 + 0.347X1 + 0.652X2 + e. Hasil uji hipotesis secara parsial dan simultan pada tingkat signifikansi 5% menunjukkan bahwa komposisi nutrisi dan harga makanan sehat berpengaruh positif signifikan terhadap keputusan pembelian produk nugget pada gen Z di Fakultas Ekonomi dan Bisnis Universitas Dharma Andalas.